Dispositivo electrónico para el control de la frecuencia respiratoria: Impacto en la reproducibilidad de la variabilidad de la frecuencia cardiaca - Carrasco Sosa, Salvador; Gaitán González, M. Jatziri; González Camarena, Ramón; Yánez Suárez, Oscar; Ríos Amezcua, Enrique (Revista Mexicana de Ingenieria Biomedica, 2001)
Usually, the respiratory frequency during heart rate variability studies is roughly controlled via the metronome sound to keep the respiratory sinus arrhythmia as fixed as possible. Besides a shortage of information, contradictory results about the reproducibility of the respiratory sinus arrhythmia have been reported. Thus, we propose a new electronic device to improve the respiratory sinus arrhythmia reproducibility through a close control of the respiratory rhythm. The device, based on a microcontroller and a column of 60 LED’s display, shows the desired rhythm to be followed by the subject. The instrument was tested on three alternate days in 11 healthy subjects breathing at 0.2 Hz during heart rate variability studies, including breathing time series. Temporal and spectral indexes of both time series were derived and their reproducibility evaluated. Intraclass correlation coefficients were from 0.81 to 0.94, which were higher than those reported in the literature. The breathing and heart rate spectra on the high frequency component presented central frequencies of 0.199 ± 0.006 vs 0.199 ± 0.008 Hz (P < 0.05), and bandwidths of 0.013 ± 0.006 vs 0.016 ± 0.008 Hz (P > 0.05), respectively. Since the device induced similar central frequencies, small bandwidths, and the reproducibility was higher than previously reported, we assume that the influence of the device was acceptable.